Effects of 3-methylmethcathinone on conditioned place preference and anxiety-like behavior: Comparison with methamphetamine - Chen, Yang; Zhang, Libo; Ding, Zengbo; Wu, Xianwen; Wang, Guibin; Shi, Jie (Frontiers in Molecular Neuroscience, 2022)
3-Methylmethcathinone (3-MMC), a drug belonging to synthetic cathinones family, raised public attention due to its harmful health effects and abuse potential. Although it has similar properties to other cathinone derivatives, the behavioral effects of 3-MMC remain largely unknown. In the present research, we evaluated the rewarding effect of 3-MMC using conditioned place preference (CPP) paradigm and its effect on anxiety-like behavior using elevated plus maze (EPM) and compared with methamphetamine (METH). Then, we performed a whole-brain c-Fos mapping to identify the specific brain regions in response to 3-MMC exposure and explored the changes of synaptic transmission in nucleus accumbens (NAc) using patch-clamp recording after chronic 3-MMC and METH exposure. 3-MMC induced CPP at higher doses of 3 or 10 mg/kg in rats and acute exposure of 3 mg/kg 3-MMC to rats produced anxiolytic-like effect, while anxiety-like behavior was increased after 7 days of injection with 3-MMC. Whole-brain immunostaining revealed increased c-Fos expression in anterior cingulate cortex (ACC), NAc and ventral tegmental area (VTA) after chronic 3-MMC injection compared with saline, which was similar to METH. Especially, 3-MMC induced more neural activation of VTA compared with METH. Finally, we found that amplitude of spontaneous inhibitory postsynaptic currents (sIPSCs) in NAc was decreased after chronic 3-MMC injection, while frequency of sIPSCs and spontaneous excitatory postsynaptic currents (sEPSCs) were not affected. Taken together, our results revealed the addictive potential of 3-MMC and its effect on anxiety-like behavior, which warn the risks of 3-MMC abuse and justify the control of synthetic cathinones. And 3-MMC selectively inhibit inhibitory but not excitatory transmission onto neurons in NAc, which may contribute to its effects.